Late onset of injection site reactions after vaccination with the 13-valent pneumococcal conjugate vaccine in adult study populations. Issue 8 (3rd August 2018) - Juergens, Christine; Trammel, James; Shoji, Yasuko; Patterson, Scott; Watson, Wendy; Webber, Chris; Gruber, William C.; Scott, Daniel A.; Schmoele-Thoma, Beate
ABSTRACT: Injection site reactions (ISRs; redness, swelling and pain) commonly occur within 1–2 days after vaccination. After administration of toxoid vaccines including diphtheria toxoid, a later onset of ISRs has also been observed. As the serotype capsular polysaccharides in the 13-valent pneumococcal conjugate vaccine (PCV13) are conjugated to cross-reactive material 197 (CRM197 ), a nontoxic variant of diphtheria toxin, the onset of ISRs over 14 days was explored in 8 adult studies with 19 cohorts. Subjects received PCV13 with aluminum phosphate (AlPO4, n = 5667) or without AlPO4 (n = 304); 1097 subjects received 23-valent pneumococcal polysaccharide vaccine (PPSV23). Late ISRs with onset between days 6–14 were observed in 8/8 cohorts aged ≥65 years after PCV13 with AlPO4 (incidence across cohorts for redness, 2.3%-19.6%; swelling, 0.9%-10.8%; pain, 1.6%-10.0%) and in 1/1 cohort after PCV13 without AlPO4 (redness 10.5%; swelling 7.5%; pain 12.3%); and in 2/4 cohorts aged 50 to 64 years after PCV13 (redness 3.1%-4.8%; swelling 1.0%-3.2%; pain 3.7%-5%). Late ISRs were not generally observed in 1/1 cohort aged 18 to 49 years after PCV13; in 2/2 cohorts aged ≥53 years after PCV13 revaccination; and in 3/3 cohorts aged ≥60 years who received PPSV23, which does not contain CRM197 . Post hoc analysis demonstrated numerically higher pneumococcal immune responses in subgroups with late ISRs versus those without. In conclusion, causality of late ISRs is likely multifactorial, with age and the PCV13 carrier protein CRM197 potentially associated. AlPO4, a vaccine adjuvant, did not appear causally related. Observations do not affect the favorable risk-benefit profile of PCV13.